Organ preservation in rectal cancer – Challenges and future strategies. (April 2017) - Gani, C.; Bonomo, P.; Zwirner, K.; Schroeder, C.; Menegakis, A.; Rödel, C.; Zips, D.
Abstract: Neoadjuvant radiochemotherapy with subsequent total mesorectal excision is the standard of care for locally advanced rectal cancer. While this multimodal strategy has decreased local recurrences rates below 5%, long-term morbidities are considerable in terms of urinary, sexual or bowel functioning. At the same time approximately 10–20% of patients have no evidence of residual tumour in their surgical specimen. Pioneering studies from Brazil have suggested that surgery can safely be omitted in carefully selected patients with a clinical complete response after radiochemotherapy. Although confirmatory studies showed similar results, challenges in terms of optimizing radiochemotherapy for organ-preservation, appropriate selection of patients for non-operative management and the safety of this approach remain. The present review will summarize the current data on organ-preservation in rectal cancer and discuss the challenges that need to be addressed in future trials.